Embedding Character Values to Children in Bugis Family Nurture - Salmiati, Salmiati; Zaman, Badru (AIBPM Publisher, 2021)
Family nurture is one of parents’ attempts to guide and lead their children physically and mentally from born to adulthood. The family has a significant role in preparing individuals in the early stages of development of their members. Family members are expected to have an active role in the community where they live. Values, norms, and practices embedded in primary socialization are influenced by family background involving ethnicity, religion, culture, and social strata. This causes children to acquire character values slowly and below the parents’ expectations. This study aimed at obtaining information on children character values inculcation in Bugis family nurture as it has been stated in Law number 20 Year 2003. This study indicated that there was character values inculcation to children in Bugis family nurture. One of the parents’ roles was to inculcate noble values to children from birth to adulthood. To realize this mission, it was crucial to strengthen the character values and the Bugis family nurture as well as to cooperate with the people within the community, messages in the Bugis community to children occur through the process of socialization and enculturation. Socialization through a verbal process, namely through advice, advice, advice and also actions in the form of parents giving examples of what is good and not good for children, while the enculturation process occurs through habituation by children to the values learned from parents and to their children. surrounding environment.